ADTH-05 Percutaneous transhepatic cholangioscopy in the treatment of biliary ductal stones. (8th June 2018) - Goodchild, George; Potts, Jonathan; Burr, Nick; Keane, Margaret G; Chapman, Michael H; Johnson, Gavin J; Pereira, Stephen P; Huggett, Matt; Webster, George J
Abstract : Introduction: Percutaneous direct cholangioscopy may expand diagnostic and treatment options where endoscopic biliary access is precluded by post-surgical anatomy. We aim to report the utility of percutaneous transhepatic cholangioscopy in patients with intrahepatic stone disease, using the SpyGlass DS cholangioscopy system. Methods: Five patients underwent percutaneous cholangioscopy between July '17 and February '18. All had post-surgical duodenal anatomy and intrahepatic duct (IHD) stones, three with an associated anastomotic stricture. In all cases prior percutaneous transhepatic cholangiography (PTC) and biliary access was achieved using conventional interventional radiology techniques, with the transhepatic tract dilated to 12 F, and a drain left in situ . Results: The procedures are summarised in Table 1. Five procedures were performed under general anaesthetic and one with sedation, with the patient supine. All patients received antibiotic prophylaxis. Under sterile conditions the cholangioscope was introduced percutaneously into the intrahepatic biliary tree via a peel-away sheath (12Fr in 5 cases and 11Fr in 1). Optimal stone localisation was achieved using fluoroscopy and direct visualisation, allowing application of electrohydraulic lithotripsy (EHL) using a Boston Scientific EHL probe for stone fragmentation. In one case 8 mm-10 mm sequential dilatation of an anastomotic stricture was performed. In one case a surgical stitch across the anastomosis was visualised – the likely nidus for stone formation. Stone clearance was successful in all cases where IHD stones were identified. In one case the IHD stones had cleared since the index PTC. There were no recorded procedural complications. Conclusion: In this small case series direct visualisation of the biliary tree using percutaneous SpyGlass cholangioscopy was safe, successful and expanded the therapeutic capabilities of PTC. This technique could also be used to enhance the investigation and treatment of post-surgical biliary anastomotic stricturing, where retrograde endoscopic access is not feasible.